Circular RNA RBPMS inhibits bladder cancer progression via miR-330-3p/RAI2 regulation - Chen Yang; Zezhong Mou; Zheyu Zhang; Siqi Wu; Quan Zhou; Yiling Chen; Jian Gong; Chenyang Xu; Yuxi Ou; Xinan Chen; Xiyu Dai; Haowen Jiang (Elsevier, 2021)
Bladder cancer is a severe cancer with high mortality because of invasion and metastasis. Growing evidence has revealed that circular RNAs play critical roles in biological function, which is closely connected to proliferation and invasion of bladder cancer. In our study, we employed qRT-PCR, RNA fluorescence in situ hybridization (FISH), 5-ethynyl-2'-deoxyuridine (EdU), CCK-8, Transwell assays, luciferase reporter assays, xenografts, and live imaging to detect the roles of circular RNA binding protein with multiple splicing (circRBPMS) in bladder cancer (BC). Bioinformatics analysis and WB were performed to investigate the regulatory mechanism. Expression profile analysis of circular RNAs (circRNAs) in BC revealed that circRBPMS was significantly downregulated. Low circRBPMS expression correlates with aggressive BC phenotypes, whereas upregulation of circRBPMS suppresses BC cell proliferation and metastasis by directly targeting the miR-330-3p/ retinoic acid induced 2 (RAI2) axis. miR-330-3p upregulation or silencing of RAI2 restored BC cell proliferation, invasion, and migration following overexpression of circRBPMS. RAI2 silencing reversed miR-330-3p-induced cell invasion and migration as well as growth inhibition in vitro. Moreover, through bioinformatic analysis of the downstream target of RAI2 in the TCGA database, we identified and validated the biological role of circRBPMS through the RAI2-mediated ERK and epithelial-mesenchymal transition (EMT) pathways. We summarize the circRBPMS/miR-330-3p/RAI2 axis, where circRBPMS acts as a tumor suppressor, and provide a potential biomarker and therapeutic target for BC.